Designing an oral insulin delivery system based on milk exosomes for managing diabetes: in vitro and in vivo investigation - Sadegh Dehghani; Reza Zolfaghari; Seyed Mohamaad Taghdisi; Khalil Abnous; Mona Alibolandi; Mohammad Ramezani (Nanomedicine Journal)
Objective(s): Oral drug administration is a noninvasive, painless, and convenient strategy that eliminates the need for routine injection routes. In recent years, milk-derived exosomes (Mexos) have gained tremendous interest as vehicles for oral drug delivery due to their low immunogenicity, high biocompatibility, and enhanced stability. Here, we hypothesized to recruit cow Mexos as an oral delivery vehicle for preparing an exosomal insulin formulation (Mexolin).Materials and Methods: Mexos were isolated using sequential ultracentrifugation steps, and insulin was loaded into the Mexos using the sonication method. Next, the encapsulation efficiency (EE) and drug loading capacity (LC) were measured using the reverse-phase high-performance liquid chromatography (RP-HPLC) strategy. Finally, following inducing and confirming diabetes in male Sprague-Dawley rats, diabetic rats were orally administered the Mexolin NPs, insulin solution, and intact Mexos. Control gropu was received subcutaneous insulin injection.Results: Findings showed that the Mexolin NPs could release insulin in a sustained manner within a simulated intestinal medium. Meanwhile, Mexolin NPs penetrated a monolayer of polarized Caco-2 cells, confirming their ability to be absorbed through the intestinal epithelium. Animal studies exhibited that the Mexolin NPs caused a hypoglycemic response in Type 1 diabetes mellitus (T1DM) induced by streptozotocin (STZ) in rats. Orally administered Mexolin NPs (100 IU/kg) indicated higher antidiabetic activity compared to subcutaneously injected insulin (5 IU/kg) and oral insulin solution alone (100 IU/kg). In addition, Mexolin NPs showed remarkable insulin bioavailability in T1DM rats.Conclusion: Mexos could be a cost-effective alternative with better patient compliance to subcutaneous insulin injection for diabetes therapy.